Towards a Pragmatic Interoperability on the MIDAS Middleware - Ribeiro, Elivaldo Lozer Fracalossi; Jesus, Luis Emanuel Neves de; Claro, Daniela Barreiro; Moura, Natan (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2021)
Nowadays, many organizations store and publish their data and services based on the Cloud Computing paradigm. In this scenario, cloud consumers access these resources anytime and anywhere. Software as a Service (SaaS) and Data as a Service are examples of cloud services. While DaaS delivers and manages data on-demand, SaaS is a delivery model of applications in a cloud environment. However, the vast amount of social data and applications enable different formats of DaaS, such as non-structured (e.g., text), semi-structured (e.g., JSON), and structured format (e.g., Relational Database). The lack of standardization makes users dependent on a system due to the lack of interoperability among different providers. Interoperability is heterogeneous systems' ability to communicate transparently, and it is classified into syntactic, semantic, and pragmatic levels. Middleware for SaaS and DaaS (MIDAS) is a solution to provide interoperability among cloud services. Although the latest version of MIDAS promotes a semantic approach, pragmatic aspects are not addressed. This paper enhances MIDAS to provide pragmatic interoperability in a cloud environment. Our approach presents the necessary elements that MIDAS must consider to provide pragmatic interoperability among cloud services. We conduct a set of experiments to validate our pragmatic MIDAS. We evaluate the overhead of our approach, the correctness of our novel MIDAS, and the effort to implement the MIDAS middleware with dynamic pragmatic information. Results evidence that our approach is towards pragmatic interoperability among cloud services.